Manufacturing method for all-solid-state batteries

The manufacturing method for all-solid-state batteries improves adhesion between the current collecting layer and the composite material layer by using an adhesive layer and applying pressure, thereby reducing electrical resistance.

JP7666309B2Active Publication Date: 2025-04-22TOYOTA JIDOSHA KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021193905
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-30
Publication Date
2025-04-22
Estimated Expiration
2041-11-30

AI Technical Summary

Technical Problem

In the manufacturing of all-solid-state batteries, issues arise with the adhesion between the current collecting foil and the composite material layer, leading to increased electrical resistance.

Method used

A manufacturing method involving the preparation of a first current collecting layer with an adhesive layer, laminating the composite material layers and solid electrolyte layer, and applying pressure to ensure close contact and adhesion between the layers.

Benefits of technology

This method reduces air bubbles between the current collecting layer and the composite material layer, enhancing adhesion and reducing electrical resistance in all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666309000002
    Figure 0007666309000002
  • Figure 0007666309000003
    Figure 0007666309000003
  • Figure 0007666309000004
    Figure 0007666309000004
Patent Text Reader

Abstract

To provide a method for manufacturing all solid-state batteries that can improve the adhesion between the current collector layer and the composite layer.SOLUTION: A method for manufacturing an all-solid-state battery includes the steps of preparing a first current collector layer with an adhesive layer; stacking a first composite layer, a solid electrolyte layer, a second composite layer, and a second current collector layer, and preparing a laminate in which the surface of the first composite layer has a convex shape; and stacking the adhesive layer of the first composite layer of the laminate on the first composite layer, and pressing.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to all-solid-state batteries. [Background technology]

[0002] Patent Document 1 discloses an all-solid-state battery including a first current collecting foil, a first composite layer, a solid electrolyte layer, a second composite layer, and a second current collecting foil, in which the surface of the second current collecting foil facing the second composite layer is coated with a carbon material layer having an adhesive function, and the carbon material layer and the second composite layer are in close contact with each other. Patent Document 2 discloses the use of a current collecting foil having an adhesive layer including conductive particles including a base particle, a first conductive layer disposed on the surface of the base particle and formed of silver or copper, and a second conductive layer disposed on the outer surface of the first conductive layer and formed of nickel, and a binder. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-129485 A [Patent Document 2] JP 2019-21635 A Summary of the Invention [Problem to be solved by the invention]

[0004] Conventionally, when manufacturing an all-solid-state battery, a current collector foil is placed on a composite layer, and pressure is applied to restrain the current collector foil and attach it to a solid electrolyte layer. During this process, problems with adhesion between the layers can occur, resulting in high electrical resistance.

[0005] In view of the above, an object of the present disclosure is to provide a method for manufacturing an all-solid-state battery capable of improving the adhesion between a current collecting layer and a composite layer. [Means for solving the problem]

[0006] As one means for solving the above-mentioned problems, the present application discloses a method for manufacturing an all-solid-state battery, the method including the steps of: preparing a first current collecting layer having an adhesive layer; stacking a first composite layer, a solid electrolyte layer, a second composite layer, and a second current collecting layer to prepare a laminate in which the surface of the first composite layer has a convex shape; and overlaying the adhesive layer of the first current collecting layer on the first composite layer of the laminate, and pressing. Effect of the Invention

[0007] According to the manufacturing method for an all-solid-state battery disclosed herein, the amount of air bubbles remaining between the current collecting layer and the composite layer can be reduced, the adhesion between the two can be improved, and electrical resistance can be reduced. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a diagram illustrating the layer structure of an all-solid-state battery 10. [Diagram 2] FIG. 2 is a diagram illustrating the layer structure of the laminate 20. As shown in FIG. [Diagram 3] FIG. 3 is a plan view of the laminate 20. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] 1.All-solid-state battery First, an all-solid-state battery produced by the production method of the present disclosure will be described. A schematic cross-sectional view showing an example of an all-solid-state battery is shown in Fig. 1. As shown in Fig. 1, the all-solid-state battery 10 has a positive electrode composite layer 11 which is a first composite layer containing a positive electrode active material, a negative electrode composite layer 12 which is a second composite layer containing a negative electrode active material, a solid electrolyte layer 13 formed between the positive electrode composite layer 11 and the negative electrode composite layer 12, a positive electrode current collector layer 14 which is a first current collector layer that collects current from the positive electrode composite layer 11, and a negative electrode current collector layer 15 which is a second current collector layer that collects current from the negative electrode composite layer 12. The positive electrode composite layer 11 and the positive electrode current collector layer 14 may be collectively referred to as a positive electrode, and the negative electrode composite layer 12 and the negative electrode current collector layer 15 may be collectively referred to as a negative electrode. In this embodiment, the positive electrode side is referred to as "first", with the first composite layer being the positive electrode composite layer, the first current collecting layer being the positive electrode current collecting layer, and the negative electrode side is referred to as "second", with the second composite layer being the negative electrode composite layer, and the second current collecting layer being the negative electrode current collecting layer, but this may be reversed. Each component of the all-solid-state battery 10 will be described below.

[0010] 1.1. Positive electrode mixture layer Positive electrode mixture layer 11 is a layer containing a positive electrode active material, and may further contain at least one of a solid electrolyte material, a conductive material, and a binder, as necessary.

[0011] The positive electrode active material may be a known active material. For example, cobalt-based (LiCoO2, etc.), nickel-based (LiNiO2, etc.), manganese-based (LiMn2O4, Li2Mn2O3, etc.), iron phosphate-based (LiFePO4, Li2FeP2O7, etc.), NCA-based (nickel, cobalt, aluminum compound), NMC-based (nickel, manganese, cobalt compound), etc. are listed. More specifically, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc. The surface of the positive electrode active material may be covered with an oxide layer such as a lithium niobate layer, a lithium titanate layer, or a lithium phosphate layer.

[0012] The solid electrolyte is preferably an inorganic solid electrolyte, since it has higher ionic conductivity and superior heat resistance compared to organic polymer electrolytes. Examples of inorganic solid electrolytes include sulfide solid electrolytes and oxide solid electrolytes. Examples of sulfide solid electrolyte materials having Li ion conductivity include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n(where m and n are positive numbers. Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers; M is any of P, Si, Ge, B, Al, Ga, and In.) The above description of "Li2S-P2S5" means a sulfide solid electrolyte material obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.

[0013] On the other hand, examples of oxide solid electrolyte materials having Li ion conductivity include compounds having a NASICON structure. An example of a compound having a NASICON structure is a compound represented by the general formula Li 1+x Al x Ge 2-x Compounds represented by the formula (PO4)3 (0≦x≦2) (LAGP), general formula Li 1+x Al x Ti 2-x (PO4)3 (0≦x≦2) (LATP) and the like. Another example of the oxide solid electrolyte material is LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.

[0014] The binder is not particularly limited as long as it is chemically and electrically stable, and examples thereof include fluorine-based binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), rubber-based binders such as styrene butadiene rubber (SBR), olefin-based binders such as polypropylene (PP) and polyethylene (PE), and cellulose-based binders such as carboxymethylcellulose (CMC). As the conductive material, carbon materials such as acetylene black and ketjen black, and metal materials such as nickel, aluminum, and stainless steel can be used.

[0015] The content of each component in the positive electrode mixture layer 11 and the shape of the positive electrode mixture layer 11 may be the same as in the conventional case. In particular, a sheet-shaped positive electrode mixture layer 11 is preferable from the viewpoint of easily configuring the all-solid-state battery 10. In this case, the thickness of the positive electrode mixture layer 11 is preferably, for example, 0.1 μm or more and 1 mm or less, and more preferably 1 μm or more and 150 μm or less.

[0016] 1.2.Negative electrode composite layer Negative electrode mixture layer 12 is a layer containing at least a negative electrode active material, and may contain at least one of a solid electrolyte material, a conductive material, and a binder, as necessary. The solid electrolyte material, the conductive material, and the binder can be considered to be similar to those of positive electrode mixture layer 11.

[0017] The negative electrode active material is not particularly limited. In the case of forming a lithium ion battery, examples of the negative electrode active material include carbon materials such as graphite and hard carbon, various oxides such as lithium titanate, Si and Si alloys, metallic lithium and lithium alloys, and the like.

[0018] 1.3.Solid electrolyte layer In this embodiment, solid electrolyte layer 13 is a layer including a solid electrolyte material that is disposed between positive electrode mixture layer 11 and negative electrode mixture layer 12. Solid electrolyte layer 13 includes at least a solid electrolyte material. The solid electrolyte material can be considered to be the same as the solid electrolyte material described for positive electrode mixture layer 11. The shape of the solid electrolyte layer 13 may be the same as that of a conventional solid electrolyte layer. In particular, a sheet-shaped solid electrolyte layer is preferable from the viewpoint of easily configuring the all-solid-state laminated battery 10. In this case, the thickness of the solid electrolyte layer 13 is preferably, for example, 0.1 μm or more and 1 mm or less, and more preferably 1 μm or more and 100 μm or less.

[0019] 1.4. Positive electrode current collecting layer The positive electrode current collecting layer 14 collects current from the positive electrode mixture layer 11. The positive electrode current collecting layer 14 includes a positive electrode current collecting foil 14a and a carbon material layer 14b disposed on one surface of the positive electrode current collecting foil 14a. The carbon material layer 14b is overlaid on the positive electrode mixture layer 11.

[0020] [Positive current collector foil] The positive electrode current collector foil 14a may be made of a metal foil or a metal mesh. Metal foil is particularly preferred. Metals constituting the positive electrode current collector foil 14a include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. Cu and Al are particularly preferred. The thickness of the positive electrode current collector foil 14a is not particularly limited. For example, it is preferably 0.1 μm or more and 1 mm or less, and more preferably 1 μm or more and 100 μm or less.

[0021] [Carbon material layer] Carbon material layer 14b is a layer that covers the surface of positive electrode current collector foil 14a facing positive electrode mixture layer 11, and functions as an adhesive layer such that carbon material layer 14b and positive electrode mixture layer 11 are in close contact with each other.

[0022] The carbon material layer 14b preferably has an electronic conductivity (electrical conductivity) of 20 S / cm or more. This allows the carbon material layer 14b to have appropriate electronic conductivity. There is no particular upper limit to the electronic conductivity of the carbon material layer 14b, but it is preferably 200 S / cm.

[0023] The carbon material layer 14b includes at least a binder and a conductive agent. The binder that can be included in the carbon material layer 14b is preferably an acrylic binder having a glass transition point of 30° C. or less. The conductive agent that can be included in the carbon material layer 14b is preferably a carbon material such as acetylene black (AB), furnace black (FB), ketjen black (KB), or vapor grown carbon fiber (VGCF).

[0024] The volume ratio of the binder contained in the carbon material layer 14b is x (vol%), and the amount of the conductive agent is y (cm 3When the x / y value is expressed as x / y (weight per 100 g), the value of x / y is preferably 0.0028 or more. When the x / y value is 0.0028 or more, the peel strength between positive electrode current collecting layer 14 and positive electrode mixture layer 11 can be sufficiently ensured. Here, the volume ratio of the binder is the volume ratio of the binder when the volume of the binder and the conductive agent is 100 vol%. Similarly, the volume ratio of the conductive agent described below is the volume ratio of the conductive agent when the volume of the binder and the conductive agent is 100 vol%.

[0025] The volume ratio of the conductive agent used in the carbon material layer 14b is z (vol%), and the amount of the conductive agent is y (cm 3 / 100g), the value of y×z is preferably 34 or more. When y×z is 34 or more, the electronic conductivity of carbon material layer 14b is 20 S / cm or more. Therefore, when y×z is 34 or more, the electrical resistance between carbon material layer 14b and positive electrode mixture layer 11 is low.

[0026] 1.5. Negative electrode current collecting layer The negative electrode current collecting layer 15 may be made of a metal foil or a metal mesh. Metal foil is particularly preferred. Metals constituting the negative electrode current collecting layer 15 include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. Cu and Al are particularly preferred. The negative electrode current collecting layer 15 may have a coating layer on its surface for adjusting resistance. The thickness of the negative electrode current collecting layer 15 is not particularly limited. For example, it is preferably 0.1 μm or more and 1 mm or less, and more preferably 1 μm or more and 100 μm or less.

[0027] 1.6.Battery case The all-solid-state battery may include a battery case (exterior body) (not shown) for housing each component, and examples of the battery case include a laminate sheet and a stainless steel battery case.

[0028] 2. Manufacturing method of all-solid-state batteries Next, a method for producing the all-solid-state battery according to the present disclosure will be described. The manufacturing method of the all-solid-state battery disclosed herein includes a step of producing a positive electrode current collecting layer, a step of producing a laminate, and a step of laminating the positive electrode current collecting layer on the laminate.

[0029] 2.1. Process for producing the positive electrode current collecting layer In the process of producing the positive electrode current collector layer, a carbon material layer is formed on the surface of the positive electrode current collector foil. The carbon material layer can be formed by a known method. For example, a paste containing a material constituting the carbon material layer can be applied to the positive electrode current collector foil. A known method can be used as the method for applying the paste.

[0030] 2.2. Step of preparing laminate The step of preparing the laminate is a step of obtaining a laminate of a positive electrode mixture layer, a solid electrolyte layer, a negative electrode mixture layer, and a negative electrode current collector layer. The layer arrangement of the laminate is the same as that of the all-solid-state battery 10 described above.

[0031] Schematic diagrams of laminate 20, which is one example of the laminate obtained in this step, are shown in Figures 2 and 3. Figure 2 is a cross-sectional view showing the layer structure, and Figure 3 is a plan view (viewed from the positive electrode composite layer 11 side). As can be seen from FIG. 2 and FIG. 3, the laminate 20 has a convex shape such that the surface S1 on the side of the positive electrode mixture layer 11 has an apex A within the surface. That is, in the viewpoint of FIG. 2, the apex A within the surface of the positive electrode mixture layer 11 protrudes the most (is at the highest position), and all edges of the laminate A are located lower than the apex A. The position of the apex A within the surface is not particularly limited. However, from the viewpoint of applying uniform surface pressure in the pressing process described later, it is preferable that the apex A is at the center of the surface S1. Here, the height of the convexity on the surface S1 means the position in the stacking direction of the laminate 20, and is the height when the laminate 20 is placed on a horizontal surface with the negative electrode current collector layer 15 facing down. The height of the surface S1 is expressed as the difference in height between the apex A of the surface S1 and the lowest position of the edge of the surface S1 (for example, H in FIG. 2). On the other hand, there is no particular limitation on the shape of surface S2 of negative electrode current collecting layer 15, which is the surface opposite surface S1 in laminate 20. In the example of Fig. 2, surface S2 has a concave shape corresponding to the convex shape of surface S1, but is not limited thereto and may be flat or may have an irregular shape.

[0032] Furthermore, when considering surface S1 and dividing surface S1 into surfaces S11, S12, S13, and S14 by a line passing through apex A and parallel to the edge of surface S1 as shown in FIG. 3, it is preferable that part or all of the height of the edge on each surface (edge ​​F11 on surface S11, edge F12 on surface S12, edge F13 on surface S13, and edge F14 on surface S14) is lower than any position on the inner surface of that surface. As a result, surface S1 as a whole becomes lower toward each edge, with apex A being the highest point, but even if there are some unevenness in between, air bubbles will flow to the edges during pressing, so it is possible to prevent air bubbles from remaining.

[0033] Here, it is preferable that the Young's modulus of the laminate 20 is 0.5 GPa or more and 5.0 GPa or less, which can further suppress air bubbles remaining between the layers after lamination of the positive electrode current collecting layers.

[0034] The method for producing the laminate 20 to have a convex shape is not particularly limited, but for example, a roll press machine can be used. When the laminate 20 is pressed and densified, if a roll press machine is used, the laminate 20 can be made to have a convex shape due to the difference in elongation rate between the negative electrode current collector layer (negative electrode current collector foil) and the negative electrode composite layer, the solid electrolyte layer, and the positive electrode composite layer. In addition, the shape of the convex shape can be adjusted by adjusting the thickness of each layer constituting the laminate 20.

[0035] 2.3. Step of laminating the positive electrode current collecting layer onto the laminate In the step of laminating the positive electrode current collecting layer on the laminate, the positive electrode current collecting layer prepared as described above is laminated on surface S1 of the laminate 20 thus prepared, and pressure is applied. More specifically, the positive electrode current collecting layer is disposed so that the carbon material layer is in contact with the surface S1, and pressed by a uniaxial press. The pressing force (pressing pressure) is not particularly limited, but is preferably 0.1 MPa or more and 10 MPa or less.

[0036] 3. Effects etc. According to the manufacturing method of the present disclosure, air can be released between the positive electrode mixture layer and the positive electrode current collecting layer during the pressing process, and the amount of air remaining between the layers (the presence of air bubbles) can be reduced, improving adhesion, thereby reducing the cell resistance (electrical resistance) of the all-solid-state battery. EXAMPLES

[0037] The all-solid-state battery of the present disclosure will be further described below using examples.

[0038] [Fabrication of all-solid-state batteries] (Preparation of positive electrode mixture layer) Using a rolling fluidity coating device (Powrex Corporation), Li was coated in air. 1.15 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 The positive electrode active material was obtained by coating lithium niobate onto particles with O2 as the main phase. The above positive electrode active material, sulfide solid electrolyte (Li2S-P2S5 ceramics), PVDF, and VGCF (registered trademark, Showa Denko) were added to a polypropylene container in a weight ratio of 81:16.5:0.6:1.9, and stirred for 30 seconds with an ultrasonic dispersion device (UH-50, manufactured by SMT Corporation). Next, the container was permeated for 3 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.), and further stirred for 30 seconds with an ultrasonic dispersion device. Next, after permeating for 3 minutes with a shaker, an applicator was used to apply the mixture to an Al foil by the blade method. Then, the mixture was naturally dried and dried on a hot plate at 100 ° C. for 30 minutes to obtain a positive electrode composite layer.

[0039] (Preparation of negative electrode) A negative electrode active material (LTO: lithium titanate), a sulfide solid electrolyte (Li2S-P2S5 ceramics), PVDF, and VGCF (registered trademark, manufactured by Showa Denko) were added to a polypropylene container in a weight ratio of 71:23.9:3.4:1.7, and stirred for 30 minutes with an ultrasonic dispersion device. The obtained slurry was then applied onto a copper foil by a blade method using an applicator. After that, the mixture was naturally dried and then dried for 30 minutes on a hot plate at 100°C to obtain a negative electrode in which a negative electrode composite layer was laminated on a negative electrode current collector foil (negative electrode current collector layer).

[0040] (Preparation of solid electrolyte layer) A sulfide solid electrolyte (Li2S-P2S5 ceramics) and butadiene rubber (BR) were added to a polypropylene container in a weight ratio of 99:1, and heptane was added and stirred for 30 seconds with an ultrasonic dispersion device. After shaking for 3 minutes with a shaker, the mixture was applied to an Al foil by the blade method using an applicator. The mixture was then naturally dried and then dried on a hot plate at 100°C for 30 minutes to obtain a solid electrolyte layer.

[0041] (Preparation of positive electrode current collecting layer) Acetylene black as a conductive agent and an acrylic binder were weighed, and H2O was added to prepare a carbon material layer composition. Next, this carbon material layer composition was applied to one side of an Al foil as a positive electrode current collector foil to a thickness of 2 μm, and dried at 10° C. for 1 hour to obtain a positive electrode current collector layer.

[0042] (Preparation of Laminate) A negative electrode cut to 7.2 cm x 7.2 cm and a solid electrolyte layer cut to 7.2 cm x 7.2 cm were laminated together so that the negative electrode composite layer and the solid electrolyte layer were in direct contact with each other, and pressed at 1.6 t / cm. Then, the Al foil, which is the base material of the solid electrolyte layer, was peeled off, and a positive electrode composite layer cut to 7 cm x 7 cm was laminated together so that the positive electrode composite layer and the solid electrolyte layer were in direct contact with each other, and pressed at 1.6 t / cm. The Al foil, which is the base material of the positive electrode composite layer, was peeled off, and the laminate (a laminate having a convex surface S1 corresponding to the laminate 20) was obtained by pressing at 5 t / cm. The convex shape was formed during pressing as described above. The configuration of the positive electrode mixture layer surface S1 of the laminate is as follows. Example 1: Convex shape...Top height 0.10 mm, no concave portion on surface S1 Example 2: Convex shape...top height 0.15 mm, no concave portion on surface S1 Example 3: Convex shape...top height 0.20 mm, no concave portion on surface S1 Example 4: Convex shape...top height 0.22 mm, no concave portion on surface S1 Example 5: Convex shape...Apex height 0.20 mm, on surface S12 shown in Fig. 3, there is a part in the plane from apex A toward edge F12 that is lower than a point farther from apex A. However, that part exists at a position higher than edge F12. In other words, in Example 5, surface S1 does not have a convex shape in which the entire surface gradually becomes lower from apex A toward each edge, but has a part in the plane that becomes higher (rising) toward the edge, and has a part that has a concave portion. Example 6: Convex shape...Top height 0.05 mm, no concave portion on surface S1 Example 7: Convex shape...Top height 0.25 mm, no concave portion on surface S1 Comparative Example 1: Concave shape...the deepest part is 0.25 mm deep, one part within the surface S1 is the lowest, and the edge is at the highest position. Comparative Example 2: All parts of the flat surface, surface S1, are at the same height. Comparative Example 3: uneven shape... The apex height is 0.20 mm, but on surface S12 shown in Fig. 3, there is a point within surface S12 that is lower than edge F12. That is, in Comparative Example 3, surface S1 has apex A as the highest point, and in some parts of the surface, there is a portion that becomes higher (rising) toward the edge, and in some parts, there is a recess that is lower than the edge.

[0043] Furthermore, the Young's modulus was changed in each example as shown in Table 1. The Young's modulus was changed by changing the thickness of each layer, the composition, the pressing pressure, etc. Furthermore, the Young's modulus was calculated using an autograph as the differential value of the load when a constant load was applied to the laminate.

[0044] (Lamination of positive electrode current collecting layer) The above-mentioned positive electrode current collecting layer was placed on the surface (surface S1) of the positive electrode mixture layer opposite the solid electrolyte layer of the laminate, and uniaxially pressed at 150° C. and 1 MPa.

[0045] [evaluation] The cross section of the fabricated all-solid-state battery cut in the stacking direction was observed under a microscope to evaluate the presence or absence of air bubbles remaining between the positive electrode current collector foil and the positive electrode mixture layer. The results are shown in Table 1. The evaluation was based on the following criteria: cases in which bubbles with a diameter of 0.1 mm or more were present in the adhesive layer (carbon material layer) and the positive electrode composite layer were rated as "3", cases in which bubbles were present but only bubbles with a diameter of less than 0.1 mm were rated as "2", and cases in which no bubbles were present were rated as "1".

[0046] [Table 1] [Explanation of symbols]

[0047] 10 All-solid-state battery 11 Positive electrode mixture layer 12 Negative electrode composite layer 13 Solid electrolyte layer 14 Positive electrode current collecting layer 15 Negative electrode current collecting layer

Claims

[Claim 1] A method for producing an all-solid-state battery, comprising: Providing a first current collecting layer having an adhesive layer; preparing a laminate including a first composite layer, a solid electrolyte layer, a second composite layer, and a second current collecting layer, the first composite layer having a convex surface; and laminating the adhesive layer of the first current collecting layer on the first composite layer of the laminate and pressing the laminate together, The convex shape has an apex within the plane of the surface of the first composite layer, the apex protrudes most, and all edges of the laminate are located lower than the apex, The Young's modulus of the laminate is 0.5 GPa or more and 5.0 GPa or less. How solid-state batteries are manufactured.

Citation Information

Patent Citations

  • Solid oxide fuel cell and method of manufacturing the same

    JP2008300269A

  • Manufacturing method of fuel electrode support type power generation cell

    JP2012185928A

  • Composite active material secondary particle, laminate green sheet, all-solid type secondary battery and manufacturing methods thereof

    JP2017152147A

  • Laminate green sheet, laminate sintered compact, and all-solid type secondary battery and manufacturing method thereof

    JP2018077988A

  • Laminate green sheet and all-solid type secondary battery

    JP2018077989A